A Patchwork Quilt: A Qualitative Case Study Examining Mentoring, Coaching, and Teacher Induction in the Western Québec School Board - Hollweck, Trista (Université d'Ottawa / University of Ottawa, 2019)
Mentoring, coaching, and teacher induction programs continue to gain traction in school jurisdictions across Canada and internationally in an effort to address teacher attrition, support professional growth, and improve teaching and learning. Conceptualized as a patchwork quilt, this thesis by article reports on a qualitative case study that examined the Teacher Induction Program (TIP) implemented in 2009 in the Western Québec School Board (WQSB). Each manuscript or fabric block highlights a different component of the TIP that when stitched together reveals an emerging pattern of how professional learning and development, mentoring and coaching, and teacher evaluation is understood in the school district. Anchored within a social learning theoretical framework, this study asked two guiding questions: 1) What is the influence of the mentor–coach role on experienced teachers’ professional learning, practice, and well-being? And 2) How do the WQSB stakeholders perceive the impact of the TIP? Using a single case study design, data were collected from a variety of sources and stakeholder perspectives, including documents, questionnaires, semi-structured interviews, and focus groups. Using the Framework Method, data were abductively analyzed with and against the study’s theoretical and conceptual frameworks. The study’s findings indicate that the mentor–coach role has powerful potential to not only support experienced teachers’ practice-based professional learning, but also to cultivate their sense of well-being and flourishing in schools. However, tensions emerged around how different stakeholders perceived the TIP’s impact in the school district. In particular, further attention is required to clarify the purpose and process of mentoring and coaching as well as the role of teacher evaluation within teacher induction. Ultimately, this study highlights the important role an effective mentoring and coaching fellowship can play in supporting veteran teacher professional learning, practice and well-being, which then has the potential to cultivate positive transformational change in a school district.
Keywords: mentoring; coaching; teacher induction; communities of practice; professional landscapes of practice; teacher well-being; professional learning networks; teacher evaluation; flourishing